CONTRACT OF WORK AS AN INTERNATIONALIZED CONTRACT: A SUI GENERIS RELATION OF FOREIGN INVESTMENT - Saraswati, Nanda (Jurnal Media Hukum, 2015)
Contract of work is an agreement made between the government of the Republic of Indonesia with foreign companies, and or joint ventures between foreign companies with domestic legal entities to carry out exploration and exploitation in general mining or oil and gas out of the earth, in the time period agreed by both parties. One of the foreign companies in cooperation with the Indonesian government in this field is PT Newmont Nusa Tenggara which form the contract of work in the field of utilization and development of mining potential in Indonesia. However, Act No. 25 of 2007 on Investment, Chapter IV of Form and Position Enterprises in Article 5, paragraph 2 requires that the foreign investment shall be in the form of a limited liability company based on Indonesian law and domiciled in the territory of the Republic of Indonesia, unless specified otherwise by law. Therefore, a contract of work is often regarded as a national contract by many parties. Others suggested that such contract which involves foreign investment transaction is sui generis, or in other words a quasi-public international contract. This paper will discuss the foreign elements of the contract and conclude that the contract of work can be categorized as an international contract.